Biodiesel from Scenedesmus species: Engine performance, emission characteristics, corrosion inhibition and bioanalysis. (15th September 2020) - Pugazhendhi, Arivalagan; Arvindnarayan, Sundaram; Shobana, Sutha; Dharmaraja, Jeyaprakash; Vadivel, Manokaran; Atabani, A.E.; Chang, Soon Woong; Nguyen, Dinh Duc; Kumar, Gopalakrishnan
Graphical abstract: Highlights: Low viscous algal oil was produced by Scenedesmus species, using Ni catalyst and Ni(II)–Schiff base chelate promoter. Algal oil-diesel blends offer notable fuel characteristics. Green gas emissions were reduced for all the tested blends, except (NO)x . Blends exhibit notable in vitro antimicrobial and antioxidant activities. Scenedesmus species derived biodiesel possesses effective anticorrosive activities. Abstract: We herein report the extraction of biodiesel ( S1 B and S2 B) from a two dissimilar Scenedesmus species namely Scenedesmus obliquus ( S 1 ) and Scenedesmus dimorphus ( S 2 ) by means of transesterification reaction of lipid moieties, using absolute alcohol and Ni/ H2 as medium with the presence of Ni(II)–Schiff base compound as promoter to yield biodiesel. The feature of extracted micro algal lipids was investigated via ultimate, analytical along with spectral studies. The engine characteristics with the biodiesel-diesel blends ( S 1 B10, S 1 B20 & S 1 B50 and S 2 B10, S 2 B20 & S 2 B50) demonstrate that there is a slight increase in specific fuel consumption with low brake power. Additionally, decrease in the emissions of GHGs was observed with all the diesel blends, except for NOx . In addition, the blends show distinguished in vitro antimicrobial and antioxidant activities. The thermal behavior and corrosion inhibition of the biodiesel samples were analyzed.